2006
DOI: 10.1002/jcb.20785
|View full text |Cite
|
Sign up to set email alerts
|

Defining the transcriptome of accelerated and replicatively senescent keratinocytes reveals links to differentiation, interferon signaling, and Notch related pathways

Abstract: Epidermal keratinocytes (KCs) undergo highly orchestrated morphological and molecular changes during transition from proliferative compartment into growth arrested early and late differentiation layers, prior to dying in outermost cornified layers of normal skin. Creation of stratum corneum is vital to barrier function protecting against infection. Transcriptional events in KCs regulating complex processes of differentiation and host defense required to maintain constant epidermal thickness and resistance to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Previous studies (Radoja et al 2006), including our work on KC diVerentiation (Perera et al 2006a), demonstrate the involvement of a group of key regulatory genes (adhesion, ECM, proteolysis, metabolism, cell surface receptors and secreted signaling proteins, KC makers) in the KC diVerentiation pathway. Among those regulatory genes, NOTCH signaling pathway genes are known to play a major role in the regulation of diVerentiation programs in several vertebrate cell types including adipocytes (Garces et al 1997;Hendrix et al 2002;Weijzen et al 2002;Lee et al 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies (Radoja et al 2006), including our work on KC diVerentiation (Perera et al 2006a), demonstrate the involvement of a group of key regulatory genes (adhesion, ECM, proteolysis, metabolism, cell surface receptors and secreted signaling proteins, KC makers) in the KC diVerentiation pathway. Among those regulatory genes, NOTCH signaling pathway genes are known to play a major role in the regulation of diVerentiation programs in several vertebrate cell types including adipocytes (Garces et al 1997;Hendrix et al 2002;Weijzen et al 2002;Lee et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…In our previous study using monolayer cultures of KC (Perera et al 2006a), rather than EE, global gene expression proWling revealed that early conXuent KCs were somewhat similar to proliferating KCs, yet prominent diVerences were evident when compared to late conXuent KCs; which were also distinct from replicatively senescent KCs. We report here the mRNA, miRNA and long non-coding RNA diVerential gene expression proWles identiWed by using the EE culture model.…”
Section: Introductionmentioning
confidence: 99%
“…1). Notch1 has also been shown to be down-regulated in senescent keratinocytes (50) but increased in senescent endothelial cells (51). Notch1 induces apoptosis in fibroblasts (52), neural progenitor cells (53) and B cells (54, 55), while activates senescence in endothelial cells (51) when constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
“…The role of NF-κB dependent modulation of cytokine production by Notch signaling has not been explored in great detail but it is an area of likely importance. Another major class of genes related to cytokine production that are modulated by Notch in keratinocytes are genes involved in the interferon response (Nguyen et al , 2006; Perera et al , 2006). Importantly, Notch activation in keratinocytes causes selective suppression of some interferon responsive genes, while inducing others, pointing to the existence of a novel mechanism for the fine tuning of these genes, which may be of particular significance for modulation of growth-differentiation control.…”
Section: Notch As a Negative Regulator Of Keratinocyte Stem Cell Potementioning
confidence: 99%